Effect of combination of non-slip element balloon and drug-coating balloon for in-stent restenosis lesions (ELEGANT study). Issue 5 (November 2019) - Aoki, Jiro; Nakazawa, Gaku; Ando, Kenji; Nakamura, Shigeru; Tobaru, Tetsuya; Sakurada, Masami; Okada, Hisayuki; Hibi, Kiyoshi; Zen, Kan; Habara, Seiji; Fujii, Kenji; Habara, Maoto; et al.
Highlights: In-stent restenosis is still a problematic issue of coronary intervention. Non-slip element balloon (NSE) pre-dilatation reduced balloon slippage and geographical miss. NSE pre-dilatation was associated with large acute gain. Mid-term angiographic outcomes were similar between NSE and non-compliant balloon pre-dilatation. Abstract: Background: In-stent restenosis (ISR) remains a problematic issue of coronary intervention. The non-slip element balloon (NSE) is a balloon catheter with 3 longitudinal nylon elements which are attached proximally and distally to the balloon component. The expectation is that this design of balloon is able to achieve a larger lumen area due to the elements, as well as reducing balloon slippage. We investigated whether NSE pre-dilatation improves angiographic outcomes compared to a high pressure non-compliant balloon pre-dilatation, followed by a drug-coating balloon (DCB) for treatment of ISR lesions with optical coherence tomographic imaging (OCT). Methods: Patients were eligible for the study if one or more in-stent restenosis lesions were treated with a paclitaxel-coating balloon. Patients were randomized to NSE pre-dilatation (NSE group) or high pressure non-compliant balloon pre-dilatation (POBA group) in a 1:1 fashion in 17 hospitals. The primary endpoint was in-segment late loss [post minimal lumen diameter (MLD) − follow-up MLD] at 8 months. Results: One hundred and five patients were allocated to each group. Balloon slippage (7.9% versus 22.9%, p  = 0.002) and geographical miss (6.9% versus 21.9%, p  = 0.002) were observed less in the NSE group compared to the POBA group. Acute gain was significantly larger in the NSE group (1.17 ± 0.42 mm versus 1.06 ± 0.35 mm, p  = 0.04), but post minimum stent lumen area analyzed by OCT was similar between the two groups (3.85 ± 1.67 mm 2 versus 3.81 ± 1.93 mm 2, p  = 0.64). At 8 months, average lesion length was significantly shorter than the POBA group (5.78 ± 3.26 mm versus 6.97 ± 4.59 mm, p  = 0.04), but average in-segment late loss was similar between the two groups (0.28 ± 0.45 mm versus 0.27 ± 0.38 mm, p  = 0.75). Conclusion: Eight-month angiographic outcomes were similar between NSE and non-compliant balloon pre-dilatation with DCB for treatment of ISR lesions. However, NSE pre-dilatation has advantages such as reduction of balloon slippage and geographical miss during the procedure.